Perancangan Sistem Informasi Absensi Pekerja Lapangan Berbasis Web Pada PT. Infrastruktur Digiguard Sekuriti Jakarta - Sopiyan Dalis; Syamsul Bahri; Billie Gunadi (Universitas Bina Sarana Informatika, 2021)
Abstract - Designing Web-Based Field Workers Attendance Information System on PT. Infrastruktur Digiguard Sekuriti Jakarta.In this modern era everything is done automatically using a computer. In conventional systems it takes hours to recap data, with a computerized system the process of recap data is in just minutes or seconds. Because a computerized system is more accurate, efficient and safe, it is necessary to have a computerized system in every field including the Attendance System. PT. Infrastruktur Digiguard Sekuriti is one of the companies engaged in infrastructure. Their attendance system of the field workers are still manual so that they are quite risky to errors in the absentee process. The attendance system of field workers who are still manual is also less efficient in terms of time because manual attendance recap takes long time to do.